Experimental investigations on carbonation of sodium aerosol generated from sodium fire in the context of fast reactor safety. (June 2015) - Anantha Narayanan, R.; Subramanian, V.; Sahoo, P.; Misra, Jitendra; Kumar, Amit; Baskaran, R.; Venkatraman, B.; Murali, N.
Highlights: Investigated carbonation of aerosol released from sodium fire. Investigated influence of % RH and CO2 content in air on carbonation process. Deployed a novel technique for assay of different specimens in Na-aerosol. This work can be used to predict chemical assay of aerosols in large sodium fire. Abstract: Carbonation of sodium aerosols is the most important aspects to be considered for the evaluation of chemical hazards as a part of fast reactor safety studies. The sodium oxide, immediately formed as the combustion product due to sodium fire, undergoes chemical changes to NaOH, Na2 CO3 and NaHCO3 upon reactions with moisture and CO2 prevailed in the atmosphere. Of which, hydroxide aerosols are highly corrosive and harmful, and it has stringent concentration limit for human exposure. Hence, in order to assess the condition for human intervention in the event of sodium fire, chemical composition of aerosols resulting from controlled sodium fires in a closed Aerosol Test Facility was investigated. The real time chemical species of aerosols generated from sodium fire and the effect of relative humidity (RH) and carbon dioxide concentration in air on carbonation have been studied. The experiments were carried out with the initial mass concentration of ∼4 g m −3, RH between 20% and 90% and the CO2 concentration in surrounding environment at 390 and 280 ppm. It is observed from the experimental study that aerosols are enriched with NaOH (0.8 mol fraction) in the beginning stage (samples collected during first few minutes after sodium fire) when surrounding atmosphere contains any of the following compositions – (i) ∼90% RH and 390 ppm CO2, (ii) ∼90% RH and 280 ppm CO2 or (iii) 50% RH and 280 ppm CO2 whereas they are almost equally distributed between NaOH and Na2 CO3 in the beginning stage when the atmosphere has any of the compositions (i) 50% RH, 390 ppm CO2, (ii) 20% RH, 390 ppm CO2 or (iii) 20% RH, 280 ppm CO2 . Carbonation of aerosols is completed between 20 min and 1 h just after sodium fire depending upon the prevailing atmosphere. The present study shows that highly humid condition promotes carbonation process. Faster the carbonation process the lesser would be the chemical hazard.